The Influence of Social Media Use and Self-Awareness on The Digital Ethics of FKIP UMS Students - Nafisa Fairuza Sutikno; Bambang Sumardjoko (Universitas Muhammadiyah Surakarta, 2025)
Purpose: The purpose of this study is to ascertain how social media use and self-awareness affect students' digital ethics.Methodology: The research utilizes a correlational design and a quantitative methodology. A questionnaire with twenty-two statements was used to gather data. 255 students from the UMS Faculty of Teacher Training and Education made up the research sample. The data analysis procedure employed multiple linear regression, T-test, F-test, coefficient of determination, and prerequisite tests (normality, multicollinearity, and heteroscedasticity).Results: The regression equation Y = 7.900 + 0.665X1 + 0.709X2 revealed that social media use (X1) and self-awareness (X2) had a favorable and significant impact on digital ethics. Social media (t = 6.778; p < 0.05) and self-awareness (t = 8.203; p < 0.05) have a substantial partial influence, according to the t-test, and both have a significant simultaneous effect, according to the F-test (F = 201.326; p < 0.05). 61% of the variation in students' performance is explained by the two independent factors. in students' digital ethics, according to the Adjusted R Square value of 0.612. Applications/Originality/Value: This study is important because it shows that students' digital ethics are more influenced by their level of self-awareness than by their frequency of social media use. This finding makes an original contribution by emphasizing that strengthening digital ethics needs to focus on increasing self-awareness and digital literacy. The findings of this study can be used to improve education, particularly in the areas of digital literacy and character education, in order to mold moral and responsible online conduct.